Prosedur Penerjemahan dalam Cerita Anak The Ugly Duckling - Dewi Pudjiati Alie; Maria Dita Manggarrani (Jurnal Ragam Pengabdian, 2026)
The intellectual, emotional, and social development of children can be enhanced through the introduction of language and culture. There are various types of introduction media, one of that is children's stories. This qualitative descriptive research aims to identify the translation procedures applied in the translation process of the children's story The Ugly Duckling from English into Indonesian. The data consist of micro units such as words, phrases, clauses, and sentences, analyzed using text analysis methods. The data analysis in this study employs the theory of translation procedures proposed by Peter Newmark. Based on the research findings, there are eight translation procedures used in the translation of The Ugly Duckling, namely modulation (32%), descriptive equivalent (13%), cultural equivalent (13%), reduction (13%), expansion (11%), transpositions (11%), through-translation (5%), and functional equivalent (3%)